Marianna Martines : a woman composer in the Vienna of Mozart and Haydn - Godt, Irving (Eastman studies in music., 2010)
Marianna Martines (1744-1813) composed in a wide variety of genres, vocal and instrumental, writing church music, oratorios, Italian arias, sonatas, and concertos. This book examines her life and compositional oeuvre. Based largely on eighteenth-century printed sources, archival documents, and letters (including several by Martines herself), and using many musical examples, the book presents a picture of the world in which she lived and composed in the gallant style.